Seronegative Antiphospholipid Syndrome: A Challenging Case Report - Eihab A. Subahi; Soha Aboukhalaf; Shahd Mohammedain; Sagda Sayed; Elrazi A. Ali; Mohamed Subahi; Ijaz Kamal (Clinical Case Reports)
ABSTRACT Seronegative antiphospholipid syndrome (SN‐APS) is uncommon and challenging condition, which should be included in the differential diagnosis of stroke in young, since it can result in arterial thrombosis.SN‐APS is typically diagnosed by exclusion; however, it is crucial to recognize it in order to choose the best antithrombotic treatment to lower the recurrence rate.